2017
DOI: 10.1590/0004-282x20170024
|View full text |Cite
|
Sign up to set email alerts
|

Different outcomes of phonemic verbal fluency in Parkinson’s disease patients with subthalamic nucleus deep brain stimulation

Abstract: Subthalamic nucleus deep brain stimulation (STN-DBS) is a surgical technique to treat motor symptoms in patients withParkinson's disease (PD). Studies have shown that STN-DBS may cause a decline in verbal fluency performance. We aimed to verify the effects of STN-DBS on the performance of phonemic verbal fluency in Brazilian PD patients. Sixteen participants were evaluated on the Unified Parkinson's Disease Rating Scale -Part III and for phonemic fluency ("FAS" version) in the conditions of on-and off-stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…However, STN-DBS pulse width manipulation did not reveal any significant long-term effects on verbal fluency [113]. However, the findings from studies comparing ON/OFF stimulation are inconsistent, as some studies reporting no significant effects of STN-DBS in this regard [106,109], while others reporting alterations in verbal fluency performance across various stimulation conditions [112,147,153]. There was no consistent timeframe for assessments following deactivation of DBS.…”
Section: Verbal Fluencymentioning
confidence: 96%
“…However, STN-DBS pulse width manipulation did not reveal any significant long-term effects on verbal fluency [113]. However, the findings from studies comparing ON/OFF stimulation are inconsistent, as some studies reporting no significant effects of STN-DBS in this regard [106,109], while others reporting alterations in verbal fluency performance across various stimulation conditions [112,147,153]. There was no consistent timeframe for assessments following deactivation of DBS.…”
Section: Verbal Fluencymentioning
confidence: 96%
“…The completion of VF involves accessing and self-generated search of the lexicon requiring a strategy for organizing and clustering the output, the ability to switch between exemplars (cognitive flexibility), self-monitoring and working memory (to avoid repetitions), self-initiation of responses, and inhibition of inappropriate responses. While previous literature suggests that the postsurgical decline in VF in PD is largely a surgical effect and not a stimulation effect (e.g., [8]), nevertheless the results of the studies which have examined the effect of acute STN stimulation on VF in PD are inconsistent, with some studies reporting detrimental effects of high frequency DBS [1012], others improvement of switching during verbal fluency [13], and the majority of studies finding no such effects [79, 1416]. However, two of the three studies that reported an acute effect of STN-DBS On versus Off manipulation simply examined phonemic VF and not other VF tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Outra complicação possível, é a afecção da fluência verbal (FV), apesar de se acreditar que a redução da FV seja temporária e que ela ocorra mais devido às microlesões durante a cirurgia de implante(ROMANN et al, 2017). Arten e Hamdan(2022) realizaram um estudo onde 63 indivíduos foram divididos em três grupos: o grupo ECP (16 pacientes), grupo medicamentoso (21 pacientes) e o saudáveis (26 pacientes).…”
unclassified